First Report of Fusarium oxysporum Causing Leaf Wilt on Dinteranthus vanzylii (Green Stone Plant) in China - Xue, Zhifeng (Plant disease, 2023)
Dinteranthus vanzylii is a low-growing species in the family Aizoaceae, native to southern Africa, with a pair of thick grey leaves covered with dark red spots and stripes. This stone-like succulent grows near the ground, which may protect it from water evaporation and herbivores. Dinteranthus vanzylii has become popular in China due to its attractive appearance and easy indoor cultivation. In September 2021, 7% of D. vanzylii (approximately 140 pots) showed leaf wilt symptoms in a commercial greenhouse located in Ningde (119°35'39.696″E, 27°23'30.556″N), Fujian Province, China. The diseased plants were shrivelling and eventually underwent necrosis. Their leaf tissues were rotting and carpeted with white mycelium. The leaf tissues of 10 symptomatic plants were cut into 0.5 cm2 pieces, surface-sterilized and placed on PDA medium. According to the colony morphology after 7 days of culture, 20 fungal isolates with abundant whitish aerial mycelium were divided into two types: 8 isolates produced lilac pigment whereas 12 did not. Both produced unicellular ovoid microconidia, sickled-shaped macroconidia with 3 - 4 septa and single or paired smooth, thick-walled chlamydospores on carnation leaf agar (CLA). Molecular identification based on DNA sequences from EF1-α (O'Donnell et al. 1998), RPB1 and RPB2 (O'Donnell et al. 2010) revealed 100% identity among isolates within each group; however, there were several base differences between two types. Sequences of representative isolates KMDV1 and KMDV2 were deposited in GenBank (acc. nos.: OP910243, OP910244, OR030448, OR030449, OR030450 and OR030451), which showed 99.10% - 99.74% identity with different F. oxysporum strains (GenBank acc. nos.: KU738441, LN828039, MN457050, MN457049, ON316742 and ON316741). Phylogenetic tree inferred from the concatenated EF1-α, RPB1 and RPB2 revealed that these isolates clustered with F. oxysporum. Thus, these isolates were identified as F. oxysporum. Using a root-drenching method, 10 one-year-old healthy D. vanzylii were inoculated in conidial suspensions (1*106 conidia/mL) of isolates KMDV1 and KMDV2 for 60 min, respectively. They were transplanted into pots with sterilized soil and incubated in a plant-growth chamber at 25°C and 60% relative humidity. Control plants were treated with sterilized water. The pathogenicity test was repeated three times. All plants inoculated with each isolate developed leaf wilt symptoms after 15 days and were dead after 20 - 30 days. However, no symptoms were observed in the control plants. Fusarium oxysporum was reisolated and confirmed based on morphology and EF1-α sequence analysis. No pathogens were isolated from the control plants. This is the first report of F. oxysporum causing leaf wilt disease on D. vanzylii in China. To date, several diseases have been reported on members of the Aizoaceae. For instance, collar and stem rot on Lampranthus sp. caused by Pythium aphanidermatum (Garibaldi et al. 2009), wilt on Lampranthus sp. and Tetragonia tetragonioides caused by Verticillium dahliae (Garibaldi et al. 2010; Garibaldi et al. 2013), and leaf spot on Sesuvium portulacastrum caused by Gibbago trianthemae (Chen et al., 2022). Our research could provide insight into fungal diseases on members of the Aizoaceae and contribute to their cultivation and management